Development of microgap and nanogap automated permittivity measurement system - Azizullah B. Saifullah (School of Microelectronic Engineering, 2011)
The goal of this research is to develop an electronic system that integrated with nanogap capacitor biosensor. This system is called Permittivity Measurement System (PMS). It measures the impedance value of the nanogap capacitor and calculates the permittivity value based on the parameter specification of nanogap capacitor obtained through characterization process. The parameters are gap width, internal resistance, capacitance value with no sample, and cross section area of the plate.